Seasonal predictability of tropical cyclone frequency over the western North Pacific by a large-ensemble climate model - Takeshi Doi; Tadao Inoue; Tomomichi Ogata; Masami Nonaka (npj Climate and Atmospheric Science)
Abstract We assessed the seasonal prediction skill of tropical cyclone (TC) frequency over the western North Pacific by the large-ensemble SINTEX-F dynamical system. Although the prediction skills were limited, the correlation skill for the June–August prediction issued in early May was statistically significant around Okinawa and Taiwan. Particularly, the high TC activity in summer 2018 was well predicted. We found that the 2018 positive Indian Ocean Dipole (IOD) contributed to the predictability by the dynamical prediction system: suppressed convection in the eastern tropical Indian Ocean enhanced divergent wind from the eastern tropical Indian Ocean to the Okinawa and Taiwan areas. This helped to generate low pressure in the target area, which was favorable to the TC activity. The IOD contributions to the predictability were also seen in the correlation analyses in 1982–2022 and some case studies in 1994 and 1998. This could be useful for actionable early warnings.